2020
DOI: 10.1109/ojemb.2020.2998051
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Biomarkers of COVID-19 Based on Coordination of Speech-Production Subsystems

Abstract: Goal: We propose a speech modeling and signal-processing framework to detect and track COVID-19 through asymptomatic and symptomatic stages. Methods: The approach is based on complexity of neuromotor coordination across speech subsystems involved in respiration, phonation and articulation, motivated by the distinct nature of COVID-19 involving lower (i.e., bronchial tubes, diaphragm, lower trachea) versus upper (i.e., laryngeal, pharyngeal, oral and nasal) respiratory tract inflammation [1], as well as by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 16 publications
3
80
0
1
Order By: Relevance
“…In [14] speech recordings from COVID-19 patients are analyzed to categorize automatically the health state of patients from four aspects, namely severity of illness, sleep quality, fatigue, and anxiety. Quatieri et al [26] showed that changes in vocal patterns could be a potential biomarker for COVID-19.…”
Section: Motivation and Related Workmentioning
confidence: 99%
“…In [14] speech recordings from COVID-19 patients are analyzed to categorize automatically the health state of patients from four aspects, namely severity of illness, sleep quality, fatigue, and anxiety. Quatieri et al [26] showed that changes in vocal patterns could be a potential biomarker for COVID-19.…”
Section: Motivation and Related Workmentioning
confidence: 99%
“…As the National Institute of Health is aiming at the 6 million PCR test per day, such aggressive research plan is promising to suppress this pandemic (Tromberg et al, 2020). Recently, innovative technique such as vocal biomarkars is proposed by MIT Lincoln Laboratory to identify the asymptomatic people with COVID-19 positive (Quatieri et al, 2020). Vocal change before and after infection could be detected by processing speech recording.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…A speech modeling and signal-processing framework have been proposed by Quatieri et al from MIT to detect asymptomatic and symptomatic states of COVID-19 [ 64 ]. This framework based on complex coordination pattern among neuromotor of speech subsystems indulged in articulation, respiration, and phonation which is motivated by the specific feature of COVID-19 which involves lower (bronchial, diaphragm, lower tracheal) concerning the upper (laryngeal, pharyngeal, oral and nasal) respiratory tract inflammation, also by the increased prove of the virus' neurological display.…”
Section: Digital Methods Of Sars-cov-2 Detection Mostly In Asymptomatmentioning
confidence: 99%